Gradient system processed data from the expedition AIDA, Ny Alesund, 2024 - Theresa Mathes; Christian Pilz; Louisa-Marie Otterbach; Birgit Wehner; Andreas Held (PANGAEA, 2025)
During the AIDA campaign in Ny-Ålesund, Svalbard, in spring 2024, near-surface particle and heat fluxes were measured using the gradient method. The gradient system measured the number of particles, temperature and wind speed at five heights close to the surface. We categorised the surface conditions as snow, snow/vegetation or vegetation. To measure particle concentration near the surface, we used a 1.5 m high linear actuator with a sensor board. This included a heat wire anemometer, an inlet connected to a condensation particle counter (CPC), and a distance sensor. Data about solar radiation, precipitation and wind direction and speed was, among others, provided by a weather station located at the top of the linear actuator. The gradient system was set up to approach six different height levels in sequence. Depending on the height level, the distance to the surface from the inlet varied, with measurements taken at 10 cm, 14 cm, 22 cm, 38 cm, 69 cm and 134 cm. We calculated the sensible heat flux and the particle flux using the flux-gradient relationships method. Monte Carlo simulation was utilized to estimate the uncertainty of the flux estimate due to the error of the measuring instruments.
In: Mathes, T et al. (2025): Particle flux-gradient relationships for the expedition AIDA, Ny Alesund, 2024 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984519